Risk factors and short-term respiratory outcomes associated with unplanned extubations during neonatal intensive care - Mannerstedt, Irma; Markasz, Laszlo; Karlsson, Victoria; Pettersson, Nils; Blomqvist, Ylva Thernström; Ågren, Johan; Sindelar, Richard (Frontiers in Pediatrics, 2025)
BackgroundUnplanned extubation (UE) represents an unwanted adverse event in neonatal intensive care. Although skin-to-skin care (SSC) in intubated infants receiving mechanical ventilation (MV) is challenging, its impact on the incidence of UEs has not been reported.PurposeTo determine the incidence, infant characteristics, and short-term respiratory outcomes of UEs in a unit applying SSC as standard of care also during MV.MethodsSingle-center retrospective cohort study including all infants receiving MV in a Swedish tertiary care center during 2021–2023. UE incidence was calculated per 100 days of MV related to time spent in conventional care (CC) and SSC, using automated chart review of electronic medical records. Pre-defined short-term respiratory outcomes were mode of respiratory support, ventilator settings and fraction of inspired oxygen (FiO2), at 30–120 min post-UE.ResultsThe UE incidence was 3.9 per 100 days of MV (3.0 in CC vs. 10.4 in SSC; p < 0.001). The UE incidence during SSC decreased from 14.5 in 2021, to 7.7 in 2023 (p = 0.07), whereas it remained the same during CC. After UE, 72% infants were reintubated within 120 min, and showed an increased mean FiO2 (0.37 vs. 0.43; p = 0.01).ConclusionsThe number of UEs were high during SSC but decreased during the study period. Reintubation was not required in >25% of all UEs, regardless of type of care. Following UE, an increased need for supplemental oxygen was observed. Safe SSC in mechanically ventilated infants requires experienced staff and increased staff and parental risk awareness.